Structural Engineering of Hierarchical Aerogels Comprised of Multi-dimensional Gradient Carbon Nanoarchitectures for Highly Efficient Microwave Absorption - Zhao, Yongpeng; Zuo, Xueqing; Guo, Yuan; Huang, Hui; Zhang, Hao; Wang, Ting; Wen, Ningxuan; Chen, Huan; Cong, Tianze; Muhammad, Javid; Yang, Xuan; Wang, Xinnan; et al. (Nano-Micro Letters, 2021)
Recently, multilevel structural carbon aerogels are deemed as attractive candidates for microwave absorbing materials. Nevertheless, excessive stack and agglomeration for low-dimension carbon nanomaterials inducing impedance mismatch are significant challenges. Herein, the delicate “3D helix–2D sheet–1D fiber–0D dot” hierarchical aerogels have been successfully synthesized, for the first time, by sequential processes of hydrothermal self-assembly and in-situ chemical vapor deposition method. Particularly, the graphene sheets are uniformly intercalated by 3D helical carbon nanocoils, which give a feasible solution to the mentioned problem and endows the as-obtained aerogel with abundant porous structures and better dielectric properties. Moreover, by adjusting the content of 0D core–shell structured particles and the parameters for growth of the 1D carbon nanofibers, tunable electromagnetic properties and excellent impedance matching are achieved, which plays a vital role in the microwave absorption performance. As expected, the optimized aerogels harvest excellent performance, including broad effective bandwidth and strong reflection loss at low filling ratio and thin thickness. This work gives valuable guidance and inspiration for the design of hierarchical materials comprised of dimensional gradient structures, which holds great application potential for electromagnetic wave attenuation. Highlights: 1 The delicate “3D helix–2D sheet–1D fiber–0D dot” hierarchical aerogels were successfully synthesized. 2 The graphene sheets are uniformly intercalated by helical carbon nanocoils, which endow the as-obtained aerogel with abundant porous structures and better dielectric properties. 3 By adjusting the growth parameters of 0D core-shell structured particles and 1D carbon nanofibers, the tunable electromagnetic properties and excellent impedance matching are achieved.